Ocean and Coastal Ecosystems and their Services, in: Climate Change 2022: Impacts, Adaptation and Vulnerability. Working Group II Contribution to the IPCC Sixth Assessment Report - Cooley, Sarah; Schoeman, David; Bopp, Laurent; Boyd, Philip; Donner, Simon; Ghebrehiwet, Dawit Yemane; Ito, Shin-Ichi; Kießling, Wolfgang; Martinetto, Paulina; Ojea, Elena; Racault, Marie-Fanny; Rost, Björn; et al. (Climate Change 2022: Impacts, Adaptation and Vulnerability. Working Group II Contribution to the IPCC Sixth Assessment Report, 2022)
Anthropogenic climate change has exposed ocean and coastal ecosystems to conditions that are unprecedented over millennia (high confidence2), and this has greatly impacted life in the ocean and along its coasts (very high confidence). Fundamental changes in the physical and chemical characteristics of the ocean acting individually and together are changing the timing of seasonal activities (very high confidence), distribution (very high confidence), and abundance (very high confidence) of oceanic and coastal organisms, from microbes to mammals and from individuals to ecosystems, in every region. Evidence of these changes is apparent from multi-decadal observations, laboratory studies and mesocosms, as well as meta-analyses of published data. Geographic range shifts of marine species generally follow the pace and direction of climate warming (high confidence): surface warming since the 1950s has shifted marine taxa and communities poleward at an average (mean ± very likely range) of 59.2 ± 15.5 km per decade (high confidence), with substantial variation in responses among taxa and regions. Seasonal events occur 4.3 ± 1.8 to 7.5 ± 1.5 days earlier per decade among planktonic organisms (very high confidence) and on average 3 ± 2.1 days earlier per decade for fish (very high confidence). Warming, acidification and deoxygenation are altering ecological communities by increasing the spread of physiologically sub-optimal conditions for many marine fish and invertebrates (medium confidence). These and other responses have subsequently driven habitat loss (very high confidence), population declines (high confidence), increased risks of species extirpations and extinctions (medium confidence) and rearrangement of marine food web
Keywords: anthropogenic; climate; change; geographic range shifts; range; shifts; marine; species; warming; acidification; deoxygenation; invertebrates; fish; extinctions; rearrangement